Hubungan Pola Makan Dengan Kejadian Diabetes Melitus Tipe 2 di Rumah Sakit Efarina Etaham Berastagi Tahun 2025 - Putri Dianti; Hariyantika Hariyantika; Awalia Nisa Putri (Jurnal Minfo Polgan, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by increased blood glucose levels resulting from insulin resistance and impaired insulin secretion. One of the risk factors associated with the occurrence of T2DM is dietary patterns. Unhealthy eating habits, such as consuming foods high in sugar and fat but low in fiber, can increase the risk of developing T2DM. This study aims to determine the relationship (correlation) between dietary patterns and the incidence of T2DM in the working area of a Community Health Center (Puskesmas). The study used a quantitative method with a descriptive correlational design and a cross-sectional approach. A total of 83 respondents were selected using purposive sampling. Data were analyzed using the Chi-Square test. The results showed a significant relationship between dietary patterns and the incidence of T2DM (p < 0.05). The conclusion of this study is that there is a correlation between dietary patterns and the incidence of T2DM, indicating that nutrition education and dietary behavior modification are crucial for prevention..